No child's play: Under-five child feces management in a rural area of Bengaluru Urban District, India - Anissa Mary Thomas Thattil; Twinkle Agrawal; Abdul Kader Surti; Stallon Sebastian; Kiyana Mirza; George Jacob; Farah Naaz Fathima (Indian Journal of Community Medicine, 2024)
Background: Inappropriate feces disposal leads to environmental contamination, and increases the risk of exposure to children. We aimed to estimate the proportion of rural households with knowledge and practice of safe management of feces (SMoF) among under-five children and to identify associated factors. Materials and Methods: A cross-sectional study was conducted in eight villages in Bengaluru Urban district over 2 months, using a face-validated semi-structured interview schedule. SMoF was defined based on five criteria – defecation site, transport tool, feces disposal, cleaning of transport tool, and hand washing. Results: Out of 320 under-five children surveyed, 15.7% were pre-ambulatory and 84.3% were ambulatory. The majority of the caregivers (92.5%) felt that children should defecate in the latrine and only 23.7% were aware that child feces were more infectious than adult feces. SMoF was only practiced by caregivers of ambulatory children (52.6%). Households with older caregivers (P = 0.01) and those living in a pucca house (P = 0.02) with a latrine inside (P = 0.04) were found to practice SMoF. Children of households that practiced unsafe disposal of child feces experienced more diarrheal episodes (P = 0.04). Caregivers >20 years were found to have better odds of SMoF [20–25 years (adjusted odds ratio, aOR: 9.02), 26–30 years (aOR: 12.17), >30 years (aOR: 8.93)] compared to those <20 years. Conclusion: The proportion of households with knowledge and practice of SMoF was low. Awareness of SMoF is essential to reduce the incidence of diarrheal diseases and improve sanitation. Our findings also call for awareness building at schools and colleges.